Bioplastik Alginat-Karagenan sebagai Substitusi Material Petrokimia dalam Industri Kemasan - Nainggolan, Denny Hendrik (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The escalating buildup of petrochemical based plastic waste has intensified efforts to develop sustainable bioplastics derived from renewable materials. Accordingly, this research investigates how variations in carrageenan content influence the physical and mechanical characteristics of alginate carrageenan composite bioplastics formulated with glycerol as a plasticizer. Alginate was extracted from Sargassum sp. and carrageenan from Kappaphycus alvarezii. Bioplastics were prepared using carrageenan concentrations ranging from 1.5 to 3.5 grams and characterized for tensile strength, elongation, thickness, water resistance, biodegradability, and opacity. The results indicate that carrageenan concentration significantly affects tensile strength, elongation, thickness, biodegradability, and opacity, while water resistance is not significantly influenced. The optimal formulation was obtained at a carrageenan concentration of 1.5 grams, complying with Japanese Industrial Standard and SNI 7188.7:2016. Further studies are recommended to incorporate additional materials to improve water resistance and functional performance of the bioplastics.